Cost transferability problems in economic evaluation as a framework for an European health care and social costs database - García-Mochón, Leticia (Cost Eff Resour Alloc, 2021)
This article presents part of the work within Work Package 3 (WP3) of Impact HTA (Improved methods and actionable tools for enhancing HTA), a H2020 EU-funded research project, intended to enhance and promote collaboration in HTA across EU MS. Amongst other objectives, and in close collaboration with WP4, WP3 addressed setting up a multi-country unit-cost database: the European health care and social costs database (EU HCSCD). The purpose of the database is to facilitate the transference of healthcare economic evaluation analyses across countries, jurisdictions and settings. WP3 concentrates on healthcare costs; WP4 on social costs. This paper discusses the state of the art on this topic, building an appropriate conceptual and theoretical framework for Database development. We conducted a broad, but not systematic, literature and gray-literature review (LR), identifying existing practices and problems, and their implications, described in the Results section. We discuss practical implications and draw important conclusions behind the construction, and future evolution, of this database. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12962-021-00294-4.